Educational Media Introducing Computer Devices Based on Augmented Reality for Elementary Schools - Hafizh, Maulana; Ilham Faisal; Arief Budiman (Yayasan Kita Menulis, 2025)
Early mastery of technology is a crucial step in preparing young generations to face the challenges of the digital era. Therefore, introducing computer devices to elementary school students is essential. This study aims to develop an educational media based on Augmented Reality (AR) as an interactive learning tool for introducing computer devices to elementary school students. This educational media is designed to facilitate a more engaging and immersive learning process by visualizing computer devices in three dimensions and allowing students to interact with virtual objects. Through the use of AR, students can learn about computer components such as monitors, keyboards, mice, and CPUs in a more interactive and enjoyable way. Trials conducted in several elementary schools students indicate that the use of this media improves students' understanding of computer device concepts compared to conventional teaching methods. Therefore, this AR-based educational media is expected to serve as an innovative alternative in information technology education at the elementary school level.